Endangered species condoms: a social marketing tool for starting conversations about population. (1st June 2020) - Baillie, Sarah; Dennings, Kelley; Feldstein, Stephanie
Abstract : The Endangered Species Condoms project was launched 10 years ago to bring the discussion of human population growth back into the environmental movement with a focus on human rights and reproductive justice. In that time, more than 1 million condoms have been distributed by thousands of volunteers. The principles of social marketing are used through the Endangered Species Condoms project to create a national discourse around the population issue. They are introduced in both formal teaching settings like high school and university classrooms as well as informal settings like community events and after-hours programing at zoos and museums to reach a broad, diverse audience.